2012
DOI: 10.1056/nejmoa1201569
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype versus Microarray Testing for Genetic Abnormalities after Stillbirth

Abstract: Background Genetic abnormalities have been associated with 6 to 13% of stillbirths, but the true prevalence may be higher. Unlike karyotype analysis, microarray analysis does not require live cells, and it detects small deletions and duplications called copy-number variants. Methods The Stillbirth Collaborative Research Network conducted a population-based study of stillbirth in five geographic catchment areas. Standardized postmortem examinations and karyotype analyses were performed. A single-nucleotide po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
183
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(186 citation statements)
references
References 24 publications
2
183
0
1
Order By: Relevance
“…To date, the largest newborn screening (in 20,126 unselected cases) using array-CGH analysis as a first-line test revealed that 87/20,126 (0.43%) of the neonatal cases had chromosomal imbalances (53 cases of aneuploidies, 23 deletions, and 11 duplications). 4 Reddy et al 14 reported the results of a population-based study of 532 stillbirths. In this sample, array-CGH analysis yielded more results than did karyotype analysis (87.4% vs. 70.5%), provided better detection of genetic abnormalities (aneuploidy or pathogenic CNVs, 8.3% vs. 5.8%), and also identified more genomic imbalances among 67 stillbirths with congenital anomalies (29.9% vs. 19.4%).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the largest newborn screening (in 20,126 unselected cases) using array-CGH analysis as a first-line test revealed that 87/20,126 (0.43%) of the neonatal cases had chromosomal imbalances (53 cases of aneuploidies, 23 deletions, and 11 duplications). 4 Reddy et al 14 reported the results of a population-based study of 532 stillbirths. In this sample, array-CGH analysis yielded more results than did karyotype analysis (87.4% vs. 70.5%), provided better detection of genetic abnormalities (aneuploidy or pathogenic CNVs, 8.3% vs. 5.8%), and also identified more genomic imbalances among 67 stillbirths with congenital anomalies (29.9% vs. 19.4%).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Fetal chromosomal abnormalities account for approximately 8-10% of intrauterine fetal demises occurring after 20 weeks of gestation and/or stillbirths occurring in the second or third trimester. 9,12 The etiologic analysis of pregnancy loss can provide important information for medical management, reproductive counseling, and supportive patient care. 4,13,14 Although fetal karyotyping has been used for many years to evaluate samples of products of conception (POCs), there are two primary limitations to this method.…”
Section: Introductionmentioning
confidence: 99%
“…The superior diagnostic power of CMA compared with karyotyping is well established in the pediatric and prenatal literature; however, exploration of the use of this technology for studying POC samples has been somewhat limited to date. 9,10,12,14,15,18,[20][21][22][23][24][25][26][27][28] Specifically, CMA is a particularly attractive technology for use in the study of POC samples because it is performed using extracted cellular DNA, significantly improving the likelihood of obtaining a result. Unlike karyotype analysis, CMA can even be performed on DNA extracted from formalin-fixed and paraffin-embedded tissues (FFPE), a process that is undergone by nearly every POC sample subjected to histopathological evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…the 23-kb duplication disrupting the MYH6 and MYH7 genes in a stillborn with atrial septal defect. Reddy et al [6] excluded all CNVs <500 kb in their analysis. Our finding illustrates the importance of evaluating all detected aberrations, regardless of size.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of CMA, submicroscopic aberrations have been shown to be associated with a number of conditions such as developmental delay, intellectual disability, congenital malformations and autism spectrum disorders [4,5]. The importance of such small aberrations has not yet been extensively studied in stillbirth, however a recent study by Reddy et al [6] showed that CMA increases the detection of chromosomal abnormalities considerably compared to karyotyping. Additionally, the technique does not require cell culture, and can hence be performed on DNA from macerated tissue.…”
Section: Introductionmentioning
confidence: 99%